Efektivitas Pemberian Herbal Cair pada Air Minum Terhadap Persentase Karkas Ayam Kampung - Rasyidah Mappanganro; Fiqri Wijaya; Muhammad Nur Hidayat (Jurnal Nutrisi Ternak Tropis, 2022)
Herbal ingredients are derived from various types of herbs that are processed naturally and are believed to be able to increase the metabolic process of chickens. This study aims to determine the effect of the addition of liquid herbal on the percentage of the carcass of native chickens. The livestock used in this study were 60 superior native chickens from Balitbangtan. Completely randomized design with 4 treatments and 5 replications. The treatments consisted of T0 (control), T1 (liquid herbal 3 ml/liter of water), T2 (vitachickÒ 0.5 gram/liter of water) and T3 (liquid herbal 3 ml + vitachickÒ 0.5 gram/liter of water). The data were analyzed using one-way ANOVA analysis, if the results showed significant results (P<0.05), then continued with the smallest significant difference (LSD) test to determine the difference in the mean value between treatments. The results showed that the administration of herbal medicine as an additive to chicken feed, the addition of herbal herbs and vitamins had a significant effect (P<0.05) on carcass weight and carcass percentage, but had no significant effect (P>0.05) on the final weight of native chickens. The highest average carcass percentage was at T1 61,15±1,90%, then T2 60,10±2,60%, T3 59,93±4,13%, dan T0 55,59±1,02%. Giving liquid herbal to P1 was able to increase the carcass percentage which was better than other treatments.